1987
DOI: 10.1016/s0006-3495(87)83321-0
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion- and reaction rate-limited redox processes mediated by quinones through bilayer lipid membranes

Abstract: The mediation of redox reactions through bilayer lipid membranes was studied. With an appropriate choice of electron acceptors the redox process can be limited either by the chemical reaction rate between the mediator and the reactants or by the shuttle frequency of the mediator through the membrane. Both modes were demonstrated for redox reactions mediated by 2,6 dichlorobenzoquinone (DCBQ) and by alpha-tocopherol with ascorbate entrapped inside vesicles using ferricyanide (a mild oxidant) or hexachloroiridat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 10 publications
3
13
0
Order By: Relevance
“…There have been reports suggesting a role for ␣-tocopherol in assisting the transport of electrons over the membrane (2,28). Under standard culture conditions, cells have a very low ␣-tocopherol content due to the low level of this compound in serum (29).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been reports suggesting a role for ␣-tocopherol in assisting the transport of electrons over the membrane (2,28). Under standard culture conditions, cells have a very low ␣-tocopherol content due to the low level of this compound in serum (29).…”
Section: Resultsmentioning
confidence: 99%
“…It could involve either direct chemical reactions or a membrane-based enzyme (2,28). There have been reports in the literature suggesting a nonenzymatic route of electron transport.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that ␣-tocopherol can directly transfer ascorbate-derived electrons to ferricyanide across artificial liposomal bilayers (48), although transbilayer movement of ␣-tocopherol is slow relative to quinones with short hydrophobic tails (49). To determine whether ascorbate-dependent ferricyanide reduction requires ␣-tocopherol, two types of experiment were carried out.…”
Section: Resultsmentioning
confidence: 99%
“…5, mechanism 4), especially since ␣-tocopherol is much more abundant than ubiquinol/one-10 in membranes (68). It has been shown that ␣-tocopherol can transfer electrons from ascorbate trapped within liposomes to extravesicular ferricyanide (74). We recently confirmed this reaction and found that it was associated with sparing of ␣-tocopherol and protection against lipid hydroperoxide formation (77).…”
Section: Is It Mediated By Hydrophobic Antioxidants?mentioning
confidence: 90%
“…Initial studies using dithionite reduction of ferricyanide trapped within liposomes showed that long-chain quinones were more effective electron transfer agents than were short-chain forms (72,73). However, when less hydrophobic reducing agents such as ascorbate (73,74) and sodium borohydride (75) are used, there is very little tendency for transbilayer electron transfer by long-chain quinones or semiquinones. Long-chain quinones are viewed as restricted to the center of the bilayer and incapable of movement to either membrane face (75).…”
Section: Is It Mediated By Hydrophobic Antioxidants?mentioning
confidence: 99%